2020
DOI: 10.1039/c9me00102f
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the limits of adsorption-based CO2 capture using MOFs with PVSA – from molecular design to process economics

Abstract: We have developed a simple adsorbent screening tool including process economics to evaluate adsorbents for post-combustion capture. 22 MOFs were evaluated for four difference scenarios, UTSA-16 performs inline with the benchmark zeolite 13X.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
133
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(135 citation statements)
references
References 82 publications
1
133
1
Order By: Relevance
“…Danaci et al have developed an adsorbent screening tool to evaluate adsorbents for CO 2 capture by considering process economics and other industrially relevant factors. [96] Specifically, 25 adsorbents (1 activated carbon, 2 zeolites, 22 MOFs) were evaluated with regard to performance limitations -i. e. CO 2 purity and recovery as well as costs. It was concluded that low nitrogen adsorption and adequate adsorption enthalpies are key to achieving good process performance and reducing costs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Danaci et al have developed an adsorbent screening tool to evaluate adsorbents for CO 2 capture by considering process economics and other industrially relevant factors. [96] Specifically, 25 adsorbents (1 activated carbon, 2 zeolites, 22 MOFs) were evaluated with regard to performance limitations -i. e. CO 2 purity and recovery as well as costs. It was concluded that low nitrogen adsorption and adequate adsorption enthalpies are key to achieving good process performance and reducing costs.…”
Section: Resultsmentioning
confidence: 99%
“…Considering both CO 2 adsorption energetics and uptakes, the NbOFFIVE-1-Ni (which has not been assessed in ref. 96) shows the best uptake capacity for carbon dioxide at 400 ppm together with optimal regeneration energy ( Figure 6). [48] NbOF-FIVE-1-Ni is an ideal material for carbon capture at very low CO 2 concentrations due to its peculiar structure with contracted square-channels that are functionalized with proximal fluorine moieties.…”
Section: Resultsmentioning
confidence: 99%
“…Using a reported procedure, (64) we estimated the costs of capturing CO2 from a CO2/N2 feed at 1.05 bar and 313 K with CO2 concentrations of 4.38 % (relevant to a natural gas combined cycle flue gas), 12.5 % (relevant to coal flue gas), 21 % (relevant to a cement plant) and 25.5 % (relevant to an integrated steel mill).…”
Section: Calculation Of Co2 Capture Costsmentioning
confidence: 99%
“…Summary of purity, recovery and cost calculations for MUF-16 compared to two previously reported high-performance porous materials (64). …”
mentioning
confidence: 99%
“…7,[9][10][11][12][13][14][15][16] This interest has led to the development of different screening strategies, adoption of various modelling techniques, and suggestion of a number of performance metrics for materials ranking. 7,12,14,[16][17][18][19][20] One important outcome of the recent developments in this area is the realization that adsorbent metrics (usually obtained from molecular simulations) do not directly correlate with process performance properties such as productivity and energy consumption of a particular separation process, hence should not be used as standalone criteria for materials screening. 21 A group of recent studies has proposed that to realistically predict performance of porous materials in pressure or vacuum swing adsorption (PSA/VSA) processes, one need to adopt a multiscale screening strategy where a series of molecular simulation techniques are combined with process modelling and optimization.…”
Section: Introductionmentioning
confidence: 99%